Cell Cycle, Filament Growth and Synchronized Cell Division in Multicellular Cable Bacteria - Geerlings, Nicole M. J.; Geelhoed, Jeanine S.; Vasquez-Cardenas, Diana; Kienhuis, Michiel V. M.; Hidalgo-Martinez, Silvia; Boschker, Henricus T. S.; Middelburg, Jack J.; Meysman, Filip J. R.; Polerecky, Lubos (Frontiers in Microbiology, 2021)
Cable bacteria are multicellular, Gram-negative filamentous bacteria that display a unique divi-sion of metabolic labor between cells. Cells in deeper sediment layers are oxidizing sulfide, while cells in the surface layers of the sediment are reducing oxygen. The electrical coupling of these two redox half reactions is ensured via long-distance electron transport through a network of conductive fibres that run in the shared cell envelope of the centimetre-long filament. Here we investigate how this unique electrogenic metabolism is linked to filament growth and cell division. Combining dual-label stable isotope probing (13C and 15N), nanoscale secondary ion mass spectrometry, fluorescence microscopy and genome analysis, we find that the cell cycle of cable bacteria cells is highly comparable to that of other, single-celled Gram-negative bacteria. However, the timing of cell growth and division appears to be tightly and uniquely controlled by long-distance electron transport, as cell division within an individual filament shows a re-markable synchronicity that extends over a millimetre length scale. To explain this, we propose the “oxygen pacemaker” model in which a filament only grows when performing long-distance transport, and the latter is only possible when a filament is connected to oxygen so it is able to discharge electrons from its internal electrical network.